Phosphorus utilization by corn as affected by green manure, nitrogen and phosphorus fertilizers - Muraoka, Takashi; Franzini, Vinícius Ide; Alvarez Villanueva, Felipe Carlos; Buzetti, Salatiér; Moreti, Dolorice (Pesquisa Agropecuaria Brasileira, 2012)
The objective of this work was to evaluate the utilization by corn plants of P from triple superphosphate fertilizer labeled with 32P (32P‑TSP), and of P from soil as affected by N rates and by the green manures (GM) sunn hemp (Crotalaria juncea) and millet (Pennisetum glaucum). The experiment was carried out using pots filled with 5 kg Oxisol (Rhodic Hapludox). A completely randomized design was used, in a 4x4x2 factorial arrangement, with four replicates. The treatments were: four P rates as TSP (0, 0.175, 0.350, and 0.700 g P per pot); four N rates as urea (0, 0.75, 1.50, and 2.25 g N per pot); and sunn hemp or millet as green manure. The additions of N and P by the GM were taken into account. After grain physiologic maturation, corn dry matter, P contents, accumulated P, and P recovery in the different treatments were measured. 32P‑TSP recovery by corn increased with N increasing rates, and decreased with increasing rates of 32P‑TSP. The mineral fertilizer provides most of the accumulated P by corn plants. The recovery of 32P‑TSP by corn was 13.12% in average. The green manure species influence the assimilation of 32P‑TSP by the plants.